Determination of Optimal Parameters and Feasibility for Imaging of Epileptic Seizures by Electrical Impedance Tomography: A Modelling Study Using a Realistic Finite Element Model of the Head - Fabrizi, L.; Horesh, L.; Abascal, J. F. Perez-Juste; McEwan, A.; Gilad, O.; Bayford, R.; Holder, D. S. (IntechOpen, 2011)
None